It's Organised Chaos: Organisation and Spontaneity in Anti-state riots - Arenales Lope, Alba (PARTECIPAZIONE E CONFLITTO, 2024)
Riots are a violent form of action that has received little attention compared to other forms of action within the social movements field. Frequently defined as emotional and spontaneous outbursts, participants in riots are very rarely included in the research. In the present paper, the riots that took place during the period of the so-called "troubles" (1969-1998) in the North of Ireland involving the broader republican movement will be analysed. Given its long trajectory, the intensity, and the relevance of riots within the conflict, this case offers a unique opportunity to explore areas of the research into riots that have been neglected. Findings of a qualitative project drawing on 19 in-depth biographical interviews with participants in riots as part of the Provisional Republican cause will be presented. By conceptualising anti-state riots as a bilateral tactic, my findings suggest that the prevalent definition of riots as spontaneous forms of action needs to be revisited. As will be shown, anti-state (against police and army) riots were very often planned in advance and involved a significant level of coordination. The research findings suggest treating the concept of "spontaneity" in riots, as with other forms of collective action, with a certain level of caution.